Inside Back Cover: Potential‐Induced Fine‐Tuning of the Enantioaffinity of Chiral Metal Phases (Angew. Chem. Int. Ed. 11/2019). Issue 11 (24th January 2019) - Assavapanumat, Sunpet; Yutthalekha, Thittaya; Garrigue, Patrick; Goudeau, Bertrand; Lapeyre, Véronique; Perro, Adeline; Sojic, Neso; Wattanakit, Chularat; Kuhn, Alexander
Abstract : A mesoporous metal phase imprinted with chiral cavities functions as a stationary phase in a microfluidic channel and can separate enantiomers (represented as snails with shells of opposite chirality). In their Communication on page 3471 ff., C. Wattanakit, A. Kuhn et al. apply an electric potential to a mesoporous platinum chiral stationary phase to fine‐tune the separation efficiency of racemates, such as stereoisomers of the aminoacids tryptophan and tyrosine.